MENGAPA GENERASI MUDA ENGGAN BEKERJA DI SEKTOR PERTANIAN? MODEL PERSAMAAN STRUKTURAL SEKTOR PERTANIAN DI KABUPATEN JEMBRANA - PUTRAYASA, ADI; SUKARSA, I KOMANG GDE; KENCANA, I PUTU EKA NILA (E-Jurnal Matematika; Vol 10 No 2 (2021)DO - 10.24843/MTK.2021.v10.i02.p331, 2021)
Agriculture in Bali has profound importance, namely as a natural tourist attraction and is one of the sectors with the most workers absorb as well the largest contributor to regional income for Bali Province. Currently, the agriculture sector in Bali is experiencing the problem of decreasing the workforce due to the reluctance of future generations to continue farming inherited from their families. The purpose of this paper is to identify the factors causing the reluctance of future generations to continue family farming and to study the causality of these factors to the reluctance for continuing family farming. This study uses a variance-based structural equation modeling (PLS-SEM). Internal and external motivation to continue family farming as well the perception of agricultural works are the exogenous variables, and the reluctance to continue family farming is the endogenous variable on the model. The data in this study obtained from interviewing 115 respondents in the Jembrana Regency of Bali. The study’s result justifies that internal factors, external factors, and perceptions of agricultural work influenced the reluctance to continue family farming.